Reduced darunavir dose is as effective in maintaining HIV suppression as the standard dose in virologically suppressed HIV-infected patients: a randomized clinical trial. (18th December 2014) - Moltó, José; Valle, Marta; Ferrer, Elena; Domingo, Pere; Curran, Adrian; Santos, José Ramón; Mateo, María Gracia; Di Yacovo, María Silvana; Miranda, Cristina; Podzamczer, Daniel; Clotet, Bonaventura; ,; et al.
Abstract: Objectives: Maximizing ART efficiency is of growing interest. This study assessed the efficacy, safety, pharmacokinetics and economics of a darunavir dose-reduction strategy. Methods: This was a multicentre, randomized, open-label clinical trial in HIV-infected patients with plasma HIV-1 RNA <50 copies/mL while receiving triple ART including 800 mg of darunavir once daily. Participants were randomized to continue 800 mg of darunavir (DRV800) or to 600 mg of darunavir (DRV600), both once daily. Treatment failure was defined as two consecutive HIV-1 RNA determinations >50 copies/mL or discontinuation of study treatment by week 48. The study was registered at https://www.clinicaltrialsregister.eu (trial number 2011-006272-39). Results: Fifty participants were allocated to each arm. The mean (SD) CD4+ T cell count at baseline was 562 (303) cells/mm 3 and HIV-1 RNA had been <50 copies/mL for a median (IQR) of 106.9 (43.4–227.9) weeks before enrolment. At week 48 no treatment failure had occurred in 45/50 (90%) DRV600 patients and in 47/50 (94%) DRV800 patients (difference –4%; 95% CI lower limit, –12.9%). When only patients with virological data were considered, that endpoint was met by 45/48 (94%) in the DRV600 arm and 47/49 (96%) in the DRV800 arm (difference –2.2%; 95% CI lower limit, –9.6%). Darunavir exposure was similar in the two arms. The average reduction in annual cost per successfully treated DRV600-arm patient was US$7273. Conclusions: The efficacy of a darunavir daily dose of 600 mg seemed to be similar to the efficacy of the standard 800 mg dose in virologically suppressed HIV-infected patients on triple ART. This strategy can potentially translate to substantial savings in the cost of care of HIV-infected patients.